2011
DOI: 10.1007/s10384-011-0049-8
|View full text |Cite
|
Sign up to set email alerts
|

The relation of functional visual acuity measurement methodology to tear functions and ocular surface status

Abstract: FVA measurements performed under natural blinking significantly reflected the tear functions and ocular surface status of the eye and would appear to be a reliable method of FVA testing. FVA measurement is also an accurate predictor of dry eye status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
2
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 20 publications
4
43
2
4
Order By: Relevance
“…7,11 However, these parameters were not significantly different in the affected eyes in our study compared with fellow eyes, indicating that the FVA values directly reflected AMD-induced changes in the retina. This finding is consistent with our previous study, which demonstrated that the FVA system detects visual function impairment caused by the retinal abnormality in the epiretinal membrane.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…7,11 However, these parameters were not significantly different in the affected eyes in our study compared with fellow eyes, indicating that the FVA values directly reflected AMD-induced changes in the retina. This finding is consistent with our previous study, which demonstrated that the FVA system detects visual function impairment caused by the retinal abnormality in the epiretinal membrane.…”
Section: Discussioncontrasting
confidence: 56%
“…Functional VA values may reflect changes other than those caused by AMD because changes in corneal and lens densities 9,10 as well as tear volume (measured by the Schirmer test) 7,11,12 also affected the FVA score and VMR. 7,11 However, these parameters were not significantly different in the affected eyes in our study compared with fellow eyes, indicating that the FVA values directly reflected AMD-induced changes in the retina.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…23 Another report showed that FVA testing has an acceptable reproducibility 21 and that the results correlated significantly with tear quantities, tear stability, and ocular surface vital staining scores. 24 In this study, FVA measurements revealed impaired visual acuity values compared with the values observed by conventional visual acuity measurement before treatment. Although conventional visual acuity measurement might be good for the assessment of vision at 1 point, FVA can reveal a dynamic and detailed visual acuity over time.…”
Section: Discussionmentioning
confidence: 51%